Analysis of Activities and Learning Outcomes Reviewed from the Learning Typology of Class VIII Students at Sultan Agung Puger Middle School in Mathematics Learning - Kiki Pangestu; Marsidi; Dimas Anditha Cahyo Sujiwo (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Learning typology is the type of learning or appropriate method students use to facilitate the learning process so that they find it easy to receive and process information. This research describes activities and learning outcomes regarding student learning typologies in mathematics learning. This type of research is descriptive qualitative research. The research subjects were class VIII students at Sultan Agung Puger Middle School. The instruments used in this research were observation, questionnaires, and practice questions. The results obtained are student learning activities based on their learning typology. Class VIII students at Sultan Agung Puger Middle School have a visual and kinesthetic learning typology with a percentage of visual typology of 24.5% and kinesthetic typology of 57.5%. This is based on an analysis of the three instruments used. As a result of learning activities, students become more active, and learning results are maximum or above average because students learn based on their respective typologies.